(untitled) (Journal of Hama University, 2025)
This study aimed to test the ability of the free cash flow model to evaluate the shares of companies listed on the Damascus Stock Exchange, during the period from 2017 to 2020. To achieve the objectives of the study, the real values of the shares were calculated using the free cash flow model by extracting the free cash flows and discounting them at a rate. Discounting. The results of the statistical analysis have shown that the free cash flow model is capable of significant evaluation. In addition, a comparison was made between the real values of stocks with their market values in order to determine those suitable for investment valued at less than their value and to exclude stocks valued above their value. It has been shown that stock prices It is valued at less than its real value according to the flow model, and therefore it is in the interest of investors to invest in it since its value is higher than its market price interest of investors to invest in it since its value is higher than its market price